The Stability and Elasticity in Ta-Ti-V Medium-Entropy Alloys Using First-Principles Calculations - Hu, Wenqiang; Pan, Min; Huang, Zheng; Yang, Hongwei; Wu, Hao; Pan, Liu; Cao, Zelin; Zhao, Yong (Frontiers in Materials, 2021)
Due to low neutron activity, high thermal stability and good compression strength at elevated temperatures, medium-entropy Ta-Ti-V alloys have the application potentials used in future nuclear engineering. According to experimental results, a special quasi-random structure (SQS) model and first-principles calculations is used to calculate the structural stability and elasticity of the ternary single-phase BCC Ta-Ti-V alloys with the compositions Ta24Ti14V16, Ta19Ti17V18, Ta16Ti21V17, Ta22Ti23V9 and Ta18Ti18V18. The mixing energy of five compositions is positive, which indicating there are unstable at low temperature but stable at high temperature. Meanwhile, we predict the ability of elasticity in those five compositions, and the sequence of bulk modulus is Ta24Ti14V16 > Ta19Ti17V18 > Ta18Ti18V18 > Ta16Ti21V17 > Ta22Ti23V9, and ductility as Ta19Ti17V18 > Ta18Ti18V18 > Ta22Ti23V9 > Ta24Ti14V16 > Ta16Ti21V17. In addition, the influence of element content on elastic properties shows that Ta content will increase bulk modulus of the alloys, while Ti content decrease bulk modulus as well. Higher V and Ti content are beneficial to ductility, especially V content. Higher Ta content will sharply reduce the ductility of the alloys. Our calculation has provided further theoretical mechanism for the Ta-Ti-V MEAs preparation and development.